Lagu Anak sebagai Media dalam Mendidik Karakter Anak Usia Dini - Wahyuningsih, Sri (PIAUD Universitas Islam Negeri Sunan Kudus, 2017)
This article explores the urgency of giving the character education to children at an early age. Nowadays, the values of character among teenagers have been lost. The prominent evidence of losing the character values is rampant violence and clashes among students. The problems that led to the decline of the character of children are the crisis of religious values (spirituality), cultural nobility crisis due to a globalization, and the crisis of model from parents and teachers. Therefore, the character education should be applied to children at an early age because early childhood is the golden age that will determine children’s development in the future whether physical, mental, character and intelligence. One of the ways to educate children is through the model approach of families and parents. In addition, teachers also play an important role in educating character to children. This is achieved through teachers’ model like honest, high integrity, discipline and so on. Another way is by singing kids song in the learning process. Singing is an activity that cannot be separated from the life of early childhood. Therefore, teaching and giving character values to children is more effective and easily accepted through singing. Moreover, values or moral of the song will be remembered by the children in a longer time.